Pengaruh Gaya Kepemimpinan Dan Kompensasi Terhadap Kepuasan Kerja Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Dinas Perhubungan Kabupaten Sijunjung - Aulia Rahman; Vivi Nila Sari; Marta Widian Sari (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to test how much influence Leadership Style and Compensation have on Job Satisfaction with Work Motivation as an Intervening Variable at the Sijunjung Regency Transportation Service. Data collection methods are through surveys and circulating questionnaire, with a sample of 60 respondents. The analysis method used is path analysis using smartpls. The research results showed that there was a significant influence of Leadership Style on Work Motivation. There is a significant influence of compensation on work motivation. There is a significant influence of Leadership Style on Job Satisfaction. There is a significant influence of compensation on job satisfaction. There is a significant influence of work motivation on job satisfaction. There is an insignificant influence of Leadership Style on Job Satisfaction through Work Motivation. There is an insignificant effect of compensation on job satisfaction through work motivation.